Levels of Leptin, Adiponectin, and Insulin in COVID-19 Patients - Sura Zahim HUSSEIN; Mohammad Ahmad ABDALLA (Modern Medicine)
In SARS-CoV-2 infected patients, obesity is a risk factor for the development of respiratory failure. Many pro-inflammatory adipokines and mediators are produced from adipose tissue. Blood samples were collected from 60 COVID-19 patients after three to five days from symptoms and signs were appeared like headache, fatigue, fever, and cough. All patients were diagnosed as positive COVID-19 infection with a pharyngeal swab which is positive by RT-PCR who attended to Isolated Hospital in Tikrit City in Iraq from December 2020 to March 2021 and 30 samples from healthy individuals. Levels of leptin, adiponectin, and insulin were increased in COVID-19 patients with highly significant (P≤0.01) when compared with healthy individuals. Increased levels of leptin, adiponectin, and insulin in COVID-19 patients may occur because all patients were obese with severe respiratory inflammation.